Reclassification to another sport using FC Berlin as an example - Paweł Kalinowski; Damian Jerszyński; Monika Nowakowska; Michał Pietrzak; Katarzyna Kalinowska (Nicolaus Copernicus University in Toruń, 2020)
Education through sport is widely discussed in world literature. Sport theorists emphasize the importance of the long-term process of training a player for many years as a hierarchically complex system-structured task. Nevertheless, practical actions which are taken often differ from theoretical recommendations. In many countries due to cultural, technological or financial conditions, various systems of solutions are used.          On the basis of direct observation in one of the German teams, the article attempts to discuss the benefits of retraining young athletes for another sport. These actions are taken systematically. In addition, reference was made to the dangers arising from the use of commercialized sports activities for children and youth in Poland.            Bearing in mind both theoretical justifications and practical actions taken in the German team, one can observe the positive impact of correctly diagnosing the predisposition of children starting football training and retraining for other sports activities. In addition, based on the author's experience in training work in Germany, no negative impact on the functioning of sports training or education of such action through sport was observed.